Quadricuspid Aortic Valve: Case Report and Review of the Literature - James, Karen B. (1991)
Quadricuspid aortic valve is a rare congenital anomaly that may be found unexpectedly at surgery or diagnosed preoperatively by means of echocardiography or aortography. The most common hemodynamic abnormality associated with this anomaly is aortic insufficiency. We describe a representative case involving a 62-year-old man with severe aortic insufficiency and mild aortic stenosis. At operation, the aortic valve was found to have 4 cusps. The valve was replaced with a mechanical prosthesis. The patient was released 7 days after operation and was clinically well at 6-month follow-up. (Texas Heart Institute Journal 1991;18:141-3)